A synoptic study of a Monsoon Depression in the month of September 1963 (MAUSAM, 1965)
Synoptic features associated with the formation, intensification and movement of a Bay depression in the month of September 1963 are discussed in this paper, A low pressure system from the east moved into the Bay of Bengal where it concentrated into a depression. This occurred immediately after the weakening of a typhoon over the South China Sea. The depression intensified, moved west northwestwards and recurved over north India. Recurvature of this depression could be inferred from (1) the principle of high level steering (steering level at 300 mb), (2) the shift of the 700-500 mb thickness high from west to northeast and (3) the shift of the rain belt from the west to the north of the depression centre. The recurvature was also associated with very heavy rainfall under the influence of an upper tropospheric anticyclonic flow and a trough in the westerlies, The withdrawal, of the monsoon took place from northwest India immediately after the breaking up at the depression.